Liquid Chromatography-Tandem Mass Spectrometry Method for the Determination of Vardenafil and Its Application of Bioequivalence - Kok Zheng Gan; Riyanto Teguh Widodo; Zamri Chik; Lay Kek Teh; Mohd Salleh Rofiee; Mohd Izwan Mohamad Yusof (International Journal of Analytical Chemistry)
A simple, rapid, and sensitive method of liquid chromatography-tandem mass spectrometry (LC/MS/MS) method was developed and validated for the determination of vardenafil in rabbit plasma. A simple protein precipitation method with ice-cold acetonitrile was used for plasma extraction. The mass transitions m/z 489⟶151 and m/z 390⟶169 were used to measure vardenafil and tadalafil (internal standard), respectively, with a total assay run time of 6 min. The limit of detection was 0.2 ng/mL. The assay was reproducible with intra-assay and interassay precision ranging 1.17%–9.17% and 1.31%–5.86%, respectively. There was also good intra-assay and interassay accuracy between 89.3%–105.3% and 94%–102% of the expected value, respectively. The linearity range was 0.5–60 ng/mL in rabbit plasma (r2 ≥ 0.99). The measured AUC from 0 to 24 h AUC0−24t for the test and reference formulations were 174.38 ± 95.91 and 176.45 ± 76.88, respectively. For the test, Cmax and Tmax were 75.36 ± 59.53 ng/mL and 1.42 ± 0.19 h, whereas, for the reference, these were 58.22 ± 36.11 ng/mL and 2.04 ± 0.33 h, respectively. The test formulation achieved a slightly lower AUC0−24t value (p > 0.05), higher Cmax values (p > 0.05), faster Tmax (p < 0.05), and almost equal bioavailability compared with the reference formulation.